ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELANJA WISATAWAN DOMESTIK KE PASAR SENI TRADISIONAL DI KABUPATEN GIANYAR - Subrata, I Made; Sukarsa, Made; Yuliarmi, Ni Nyoman (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
Factors that Impact Shopping Interests of Domestic Travelers to Traditional Art Market in Gianyar Region. This research was conducted at Sukawati Traditional Art Market; the number of samples taken was 120 domestic tourists who were shopping at the Traditional Market with a sampling technique using accidental sampling. The data analysis technique used was the analysis of Partial Least Square (PLS). The results showed that: 1) there was no effect of indirect product and price on the buying intensions of tourism  through satisfaction, 2) the product and price had a positive  impact on satisfaction, 3) there was no direct or indirect effect of the education and the number of dependents on the buying intensions tourism over income, 4) the education and the number of dependents had a positive significant impact on income, 5) the product and price had positive effect on the interest of tourist in shopping while the variables of education, number of dependents, satisfaction and income had no significant effect on the buying intensions of tourism.   Keywords:  domestic travelers, shopping interests, shopping tourism, traditional art market.
Keywords: omestic travelers, shopping interests, shopping tourism, traditional art market.